2018
DOI: 10.1186/s12935-018-0555-6
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition induces stem cell like phenotype in renal cell carcinoma cells

Abstract: BackgroundMetastatic dissemination of solid tumors is often initiated by reactivation of an embryonic development program, epithelial-to-mesenchymal-transition (EMT). EMT has been associated with acquiring invasiveness and resistance to conventional therapies. However, the precise role of EMT during renal cell carcinoma is still debatable and is under investigation. In this context, our study is designed to evaluate the role of cyclosporine (CsA) and transforming growth factor-β (TGFβ) administration in induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
(41 reference statements)
1
29
0
Order By: Relevance
“…The secreted cytokine TGFβ is a tumor suppressor in nontransformed cells through its cell cycle arresting activity. Tumor cells, including those from RCC, are insensitive to this effect of TGFβ and undergo metastasis-promoting EMT and acquire chemotherapy resistance (Hao et al 2019;Singla et al 2018;Tretbar et al 2019). These processes can be abrogated with HDACi in RCC cells.…”
Section: Figmentioning
confidence: 99%
“…The secreted cytokine TGFβ is a tumor suppressor in nontransformed cells through its cell cycle arresting activity. Tumor cells, including those from RCC, are insensitive to this effect of TGFβ and undergo metastasis-promoting EMT and acquire chemotherapy resistance (Hao et al 2019;Singla et al 2018;Tretbar et al 2019). These processes can be abrogated with HDACi in RCC cells.…”
Section: Figmentioning
confidence: 99%
“…Both in vivo and in vitro results in the present study showed that hsa_circ_001895 knockdown could increase E‐cadherin and decrease N‐cadherin to inhibit EMT and metastasis of ccRCC. Moreover, EMT also participates in the promotion of ccRCC cancer stemness . Considering that hsa_circ_001895 was associated with EMT of ccRCC, further investigation of hsa_circ_001895 on stemness properties of ccRCC is needed.…”
Section: Discussionmentioning
confidence: 99%
“…As non-CSCs can acquire a CSC-like phenotype during EMT [15,16] and EMT-induced cells form spheres [17], a sphere-forming assay was conducted in the RCCs. As the Caki-1 cell line was reported to form more spheres compared to Caki-2 cells [22], the Caki-1 cells were considered a positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Several RCC markers were found to be speci cally expressed in CSCs, such as CD105, ALDH1, and Oct4, although CSC markers are not unique across tumor types [12,14]. In addition, tumor cells in the non-CSC subpopulation can spontaneously undergo epithelial-mesenchymal transition (EMT) and acquire a CSC-like phenotype and surface marker expression [15][16][17]. High expression of CD44 in RCC also correlated with recurrence and poor prognosis for 5-year overall survival [18].…”
Section: Introductionmentioning
confidence: 99%